View of Port of Spain - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
This postcard offers an aerial view of the city of Port of Spain in Trinidad.
Colour: Sepia (print); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns-- (name); Trinidad and Tobago--Aerial Views